Angiografia cerebral trans-operatória - Sérgio Raupp; Solon Teruchkin; José Carrasco Vidaurre (Arquivos de Neuro-Psiquiatria)
The author recommends the use of angiography during operations for the treatment of cerebral angiomata, the procedure helping the location of fistulae with little dimensions and securing better surgical results. Seven cases of intracranial arteriovenous congenital fistulae are reported in which the neurosurgical procedure was facilitated by transoperatory angiography. There wern't technic difficulties in any occasion.